The stored energy in metals and the concept of residual microstresses in plasticity - Szczepiński, W. (Archives of Mechanics, 2001)
Different mezomechanical models were analysed in an attempt to estimate how large is the portion of elastic energy stored in plastically deformed polcrystalline metals which may be attributed to the residual microstresses, its remaining part being connected with the creation of defects inside the particular crystallites. It has been indicated that during complex plastic deformation of a metal, the portion of elastic energy stored due to the residual microstresses may be estimated with the use of the kinematical strain hardening law, in which such stresses play an important role. Such an approach is supported by results of a simple experiment.